Pulling the witness by the ear : a riddle from the medieval Ragusan sources - Lonza, Nella (Array, 2009)
Summary: Analysing the Ragusan medieval practice of designating a potential witness by pulling his ear, the author traces the same custom in the legal codes from South East Adriatic (from the islands of Mljet and Lastovo to Shkoder). Finding striking similarities with the antestatio rite in the Twelve Tables code of Roman law, and in a number of testimonies from the Roman literature, the author follows the emergence of a ritual of similar features in the early Germanic law collections (5th-8th c.), in the documents of the Austro- Bavarian region (8th-12th c.), and in the Old Slavic legal terminology. According to the author, the link between the existence of a virtually identical legal ritual in different areas and periods might be accounted by the Roman law tradition, yet basically nourished by the shared understanding of the ear as the seat of memory